Chromatin remodeling in lymphocytic function and fate: the multifaceted roles of SWI/SNF complex - Miao, Renjie; Liu, Yun; Shen, Shuo; Wang, Wenxin; Wang, Shengjun (Frontiers in Immunology, 2025)
The Switch/Sucrose Non-Fermentable (SWI/SNF) chromatin remodeling complex comprises 10-15 subunits, which modulate the arrangement, location, or conformation of nucleosomes to upregulate chromatin accessibility. During lymphocytic differentiation and functional development, the SWI/SNF complex exerts its effects by binding to specific transcription factors (TFs) or DNA sequences via its subunits, which are thereafter recruited to the promoter or enhancer regions of target genes, rendering each subunit crucial wherein. The loss of individual subunits during lymphocytic differentiation not only disrupts the targeting of the SWI/SNF complex but also impairs its chromatin remodeling function, ultimately resulting in altered differentiation of immature lymphocytes, dysfunction of mature lymphocytes, and injured immune responses. Therefore, in this paper, we focus on TFs interacting with SWI/SNF complex subunits in lymphocytes, and summarize the effects of the loss of specific subunits of the SWI/SNF complex on lymphocytic differentiation and function, as well as the modification in the expression of key genes. We also summarize the potential clinical treatments and applications targeting the loss of SWI/SNF complex subunits, and focus on the application in Chimeric Antigen Receptor (CAR) technology. In conclusion, the SWI/SNF complex is a key regulatory factor in lymphocytic biology, involved in fundamental cellular processes and closely associated with hematological diseases and immune dysfunction. However, the specific roles of SWI/SNF complex subunits in different lymphocytic subpopulations remain unclear. Future clarification of the specific functions of these subunits in different lymphocytic subsets is expected to promote the development of immunotherapy and personalized therapy.